Leadership and Governance in Primary Healthcare An Exemplar for Practice in Resource Limited Settings - Anasel, Mackfallen; Kapologwe, Ntuli; Kalolo, Albino (Taylor & Francis, 2023)
Good leadership and governance at all levels of the healthcare system is necessary for better performance of the system and health outcomes. Lack of good leadership and governance practices can lead to misuse of health system inputs such as human resources, health commodities and financial resources hence lowering the quality of services delivered. Thus, this guide was developed through collaborative efforts envisioned to respond to the needs of improving good governance practices at the primary healthcare level in resource-limited healthcare systems. Key Features: Improves the management of primary health facilities Helps the health facility managers and teams at primary healthcare level to effectively and efficiently lead and manage the facilities Enumerates practical scenarios on health issues that commonly occur in health facilities and provides alternative ways of addressing the issues raised in the scenarios